RANCANG BANGUN SISTEM INFORMASI KOPERASI SIMPAN PINJAM BERBASIS WEBSITE - I Made Dwi Kariawan; Ni Made Estiyanti; I Nyoman Purnama (Politeknik Bisnis Indonesia, 2023)
The development of technology plays a crucial role in advancing the business world, including its application within cooperatives. Abdi Guna Artha Cooperative is engaged in providing Savings and Loans Cooperative (SLC) services or Koperasi Simpan Pinjam (KSP). The record-keeping within this cooperative is still partially manual, covering member savings, loan records, and other documentation, even though they have incorporated technology into their operations. However, their recording system relies solely on software programs, and the recording process is disparate. Consequently, the report generation process is time-consuming. Data transparency between the Cooperative and its members is essential to maintain trust. To address this issue, the author has developed a web-based Savings and Loans Cooperative Information System to handle the reporting process and to enhance data transparency between the Cooperative and its members. Data transparency is highly demanded by members to ensure the safety of their funds within the Cooperative. Cases of fraud, such as embezzlement of funds by cooperative managers, can be prevented because every transaction is promptly documented and recorded in the system. As a result, members can monitor all their savings and loan transactions, thus fostering trust between the Cooperative and its members.